Tropical architecture and music education: guidelines of environmental comfort - Valverde-López, Milena (2014)
Environmental comfort of a person from an architectural perspective, are linked to variables generated by the surrounding environment : wind, light, shadow, space design, etc. . The main functions of architecture , optimizing the quality of internal environmental comfort is highlighted. In a music center, this comfort incorporates a primary endpoint, called acoustic comfort, which incorporates new design guidelines and use of materials , fundamental for optimizing space. However, these guidelines recommend , in most cases, be implemented in closed and tight spaces , in order to gain absolute control of the sound waves . This research seeks to find a balance between the design of a tropical space, and acoustic patterns needed for music studio, making the most of natural energy from the environment and tropical climate of the area. To do this, cases nationally and internationally are analyzed, the user studies, and the results based on discussion and bibliographic information obtained in the investigation is generated.